Diffuse hair loss related to lithium use: A case report - Kulo?lu, Murat; Atmaca, Murad; Geçici, Ömer; Tezcan, A. Ertan (My University, 2000)
Lithium is a drug that has been using in management and prophylaxis of bipolar affective disorders most frequently. It has been reported that lithium have dermatologic side effects including hair loss. In many studies, the majority of patients using lithium have been reported hair loss, especially in women. In this article, a case of diffuz hair loss who was developed after the beginning of lithium treatment and improved by cessation lithium was presented because of its rarity and importance.
Lityum kullanimina ba?li yaygin saç dökülmesi: Bir olgu sinumu
Keywords: Hair loss; Lithium; Manic episode